Finding the Nearest Blood Donors using Dijkstra Algorithm - Md. Sabir Hossain; Nayan Das; Muhammad Kamrul Hossain; Md. Al-Hasan (SISFORMA, 2018)
Now-a-days frequent mishaps like the road accident or other life-risking accident leading to operational emergencies are increasing day by day and the blood donor for such victims or patients are very hard to find in a short period. Sometimes it is really tough to collect the blood of the same group from the relatives of a patient in dying moments. The main objective of this work is to make a connection with these two groups who are in need of blood and who are willing to donate. We have determined the shortest distance between blood seeker and blood donors using the Dijkstra Algorithm. Anybody can contact the nearest blood donor of any group in a particular area quickly. By implementing this idea, the harassment of the victim can be lessened and so many lives can be saved.